Bone Turnover Markers and Bone Histomorphometry in Pubertal Rats with Intrauterine Growth Restriction. (6th October 2021) - Luo, Kaiju; Chen, Pingyang; He, Mingfeng; Yang, Yonghui; Chen, Juncao; Wang, Tao
Abstract: Objective: To investigate the effect of malnutrition during pregnancy on bone development in rat pups with intrauterine growth restriction (IUGR). Methods: IUGR offspring were induced with a 10% low protein diet, while the control group was given a 21% protein diet during pregnancy. Serum biomarkers including bone glutamyl protein (BGP), amino-terminal propeptide of type 1 procollagen (P1NP), cross linked N-telopeptide of type I collagen (NTX), and insulin like growth factor 1 (IGF-1) levels were measured at 7, 21 and 56 d. Left femurs taken at 56 d were used for bone histomorphometry analysis by micro-computed tomography (micro-CT). Results: Compared with the control group, the IUGR group had lower IGF-1 and BGP levels at 7 and 21 d, and higher P1NP and NTX levels at 7 d. The IUGR group had thinner trabecular thickness (Tb.Th), lower trabecular number (Tb.N), and increased trabecular separation (Tb.Sp) at 56 d. Conclusion: The effect of IUGR on bone development may persist after birth.